Adsorption of Pharmaceuticals and Personal Care Products on Granular Activated Carbon (2016)
ABSTRACT: We investigated the adsorption to granular activated carbon of two pharmaceuticals (carbamazepine and sildenafil citrate) and a personal-care product (methylparaben) in aqueous solution, characterized the carbon, and evaluated its influence on the kinetics and adsorption equilibrium of the compounds under study. We adjusted data for the analysis of equilibrium to Langmuir and Freundlich models of adsorption isotherms and described adsorption rate using pseudo first- and second-order models; that same analysis was made on the basis of the behavior of the initial rate. In addition, we analyzed the potentiality of a nonlinear adjustment for studying kinetics and equilibrium of adsorption, an approach requiring neither knowledge of equilibrium conditions nor a-priori hypothetical suppositions regarding the order of reaction. The results indicated that the nonlinear model was capable of describing adsorption kinetic behavior, in order to determine concentrations adsorbed at equilibrium, adsorption rates of the system, maximum adsorption capacity, and global rate constant. Granular carbon exhibited an adsorption capacity for carbamazepine and methylparaben of ca. 323 mg/g and for sildenafil citrate of ca. 142 mg/g, though with slow adsorption kinetics characterized by average adsorption times of at least 168 h.